Efforts to settle government project construction work contract disputes through mediation - M. Husni T. A Ingratubun (JPPI (Jurnal Penelitian Pendidikan Indonesia))
This study aims to identify and analyze the procedures for resolving government project construction contract disputes between service users and service providers through arbitration and to analyze the legal force of arbitration decisions on disputes in construction contracts. The research approach used in this research is empirical and normative legal research. The population in this study were all contractors in the Papua Province, while the sample of this study was the party representing the government as the assignor of the Public Works and Public Housing (PUPR) in Papua Province. The data analysis method used in this study is a qualitative descriptive analysis method. The conclusion that can be drawn from this research is the settlement of construction contract disputes between PT. Kusman Jaya Papua and the Public Works Department to pay for the lack of payment for the construction of the Autonomous Office Building. Settlement of disputes through arbitration must be agreed upon by both parties. The verdict is to grant the petitioner's claim, namely regarding compensation for late payments, punish, and pay fines for the delay in the construction of the autonomous office building.